Modeling and analysis of microchannel autothermal methane steam reformer focusing on thermal characteristic and thermo-mechanically induced stress behavior. (3rd June 2021) - Li, Zheng; Yang, Guogang; Li, Shian; Shen, Qiuwan; Yang, Facai; Wang, Han; Pan, Xinxiang
Abstract: The application of fuel cells boosts the hydrogen demand particularly for distributed hydrogen production facility. As a potential candidate of hydrogen supply, microchannel autothermal methane steam reactor operates at high temperature and results in high thermal impact, which would decrease its stability and lifespan. A three-dimension numerical model based on finite element method was developed to evaluate the thermal characteristic and thermo-mechanically induced stress behavior of the reactor. Three different potential manufacturing materials, Fe–Cr–Al alloy, ceramic and quartz, were chosen. The results indicate that the cold-spot temperature appears near reactor inlet while the hotspot temperature appears near reactor outlet for reactor manufactured by different materials. Corresponding to the hot spot temperature, the maximum Von Mises stress appears near reactor outlet. The difference is the maximum Von Mises stress appears in catalyst layer for quartz reactor while it appears in interconnect rib for both Fe–Cr–Al alloy reactor and ceramic reactor. Meanwhile the maximum Von Mises stress reaches 1830 MPa for ceramic reactor. While the maximum Von Mises stress is 1197 MPa for quartz reactor and 1760 MPa for Fe–Cr–Al alloy reactor respectively. It implies the outlet catalyst layer region is vulnerable for quartz reactor. While the outlet interconnect rib is most vulnerable for both Fe–Cr–Al alloy reactor and ceramic reactor. Highlights: A coupled thermo-chemo-mechanical mathematical model of microchannel methane steam reformer was developed. The first thermal stress analysis of a microchannel reactor was performed. The cold-spot was found near the inlet while hot spot was found near the outlet. The most dangerous area of reactor manufactured by different materials was predicted.